Topographies of the Obsolete: Site Reflections - Mydland, Anne Helen; Brownsword, Neil (UK Topographies of the Obsolete Publications, 2015)
This publication in part documents the site-specific outcomes realised in a major exhibition output of the project, Vociferous Void (2013), and draws a series of commissioned essays together with the reflections of a number of participating artists, that contribute to and extend the discourse that surrounds specific research strands. The texts function as integral elements in the dissemination of the artistic research journey, which illuminate and contextualise the different modes of research, embodied within creative outputs that would otherwise remain dimly felt. They expose the processes through which works are conceived and developed, and explore the decisions, questions and issues that are confronted and reflected upon in the realm of experience rather than in the realm of cognition.